2013
DOI: 10.1103/physreve.88.042411
|View full text |Cite
|
Sign up to set email alerts
|

Role of the sample thickness in planar crack propagation

Abstract: We study the effect of the sample thickness in planar crack front propagation in a disordered elastic medium using the random fuse model. We employ different loading conditions and we test their stability with respect to crack growth. We show that the thickness induces characteristic lengths in the stress enhancement factor in front of the crack and in the stress transfer function parallel to the crack. This is reflected by a thickness-dependent crossover scale in the crack front morphology that goes from from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Scalar models are commonly used to study the planar crack front propagation in disodered elastic media [20,21], in quasi-two dimensional geometries [22] and under antiplane shearing conditions [23]. On the other hand, recent experiments have been provided the evidence that classical shear cracks singular solutions, originally devised to account for brittle fractures, offer a quantitative excellent description of the static-to-dynamic friction transition [24].…”
Section: Introductionmentioning
confidence: 99%
“…Scalar models are commonly used to study the planar crack front propagation in disodered elastic media [20,21], in quasi-two dimensional geometries [22] and under antiplane shearing conditions [23]. On the other hand, recent experiments have been provided the evidence that classical shear cracks singular solutions, originally devised to account for brittle fractures, offer a quantitative excellent description of the static-to-dynamic friction transition [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of fracture in thin-film geometries have shown that sample thickness affects the form of the elastic kernel in non-hierarchical systems [33]. In that case, film thickness is found to introduce a characteristic length scale, which effectively cuts off long-range elastic interactions along planar crack fronts.…”
Section: Discussionmentioning
confidence: 91%
“…However, a direct numerical simulation reveals to be a difficult pathway to reaching definitive conclusions, as results are prone to slow corrections to scaling, and become expensive in computational power as one moves to two or three dimensions. [10] Nevertheless, those simulations could demonstrate quite clearly that the weakest link approach could not be applied at the smallest scales. Therefore, it was already clear from the start that neither approach based on prior defect statistics only nor on a more sophisticated interaction model but within a homogeneous medium description were applicable, and hence the merit of the statistical laws and the attached corresponding size effects could be questioned.…”
Section: Introductionmentioning
confidence: 98%